2012
DOI: 10.1590/s1516-89132012000100020
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and Chromium Toxicity to Pseudokirchneriella subcapitata and Microcystis aeruginosa

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Among the metals of greatest environmental concern (Cd, Pb, and Zn), Cd was considered to have a major role in the toxicity exerted by water extracts due to its concentration (surpassing the US EPA criterion in all samples) and the significant correlation found with the toxicity to algae. However, cadmium alone was not sufficient to explain the observed toxicity since Cd contents in the extracts were markedly lower than IC50 and LC50 values estimated for R. subcapitata (67 µg L -1 ) and D. magna (101.17 µg L -1 ) by Rodgher et al (2012) and Shaw et al (2006) respectively. Nonetheless, previous studies by Biesinger et al (1986) and Barata et al (2002) reported additive effects in Cd-Zn mixtures that led to a toxicity increase, which could better explain the toxicity of the extracts.…”
Section: E Co To XI Co Lo G Ica L Ev a Lu A Tio Nmentioning
confidence: 67%
“…Among the metals of greatest environmental concern (Cd, Pb, and Zn), Cd was considered to have a major role in the toxicity exerted by water extracts due to its concentration (surpassing the US EPA criterion in all samples) and the significant correlation found with the toxicity to algae. However, cadmium alone was not sufficient to explain the observed toxicity since Cd contents in the extracts were markedly lower than IC50 and LC50 values estimated for R. subcapitata (67 µg L -1 ) and D. magna (101.17 µg L -1 ) by Rodgher et al (2012) and Shaw et al (2006) respectively. Nonetheless, previous studies by Biesinger et al (1986) and Barata et al (2002) reported additive effects in Cd-Zn mixtures that led to a toxicity increase, which could better explain the toxicity of the extracts.…”
Section: E Co To XI Co Lo G Ica L Ev a Lu A Tio Nmentioning
confidence: 67%
“…At low metal ion concentrations, active transport is favored by the cell [156]; trace concentrations of heavy metals in municipal wastewater usually do not inhibit significantly the growth of the algal consortium. Many algae strains even show high tolerance to trace amounts of Hg, Cd, Pb and Cr [58,[159][160][161][162].…”
Section: Heavy-metal Contamination In Wastewatermentioning
confidence: 99%
“…[40], and Isochrysis galbana [41]. Then again, other species seem to be more sensitive to Cd, for instance, Scenedesmus obliquus (EC 50 = 0.058 mg/L) [42], Nitzschia palea (0.0276 mg/L) [43], and Pseudokirchneriella subcapitata (0.6 µM) [44]. C. acidophila has also shown an intraspecific variation in Cd tolerance.…”
Section: Cytotoxicity and Ros Inductionmentioning
confidence: 99%